The management of very low-calorie ketogenic diet in obesity outpatient clinic: a practical guide - Muscogiuri, Giovanna (J Transl Med, 2019)
The epidemic of obesity is growing steadily across the whole world. Obesity is not only a merely aesthetic disease but is the “mother” of most chronic diseases such as associated with a range of type 2 diabetes, cardiovascular disease, obstructive sleep apnea, and cancer. However, although there is a need to find a strategy to stop this epidemic disease, most of the times the current nutritional strategies are not effective in weight loss and in long term weight maintenance. Very low-calorie ketogenic diets (VLCKD) is increasingly establishing as a successful nutritional pattern to manage obesity; this is due to rapid weight loss that gives rise to a positive psychological cycle which in turn increases the compliance to diet. Another important key point of VLCKD is the ability to preserve fatty free mass which is known to play a role of paramount importance in glucose metabolism. Despite the clinical evidence of VLCKD there are paucity of data regarding to its management. Therefore, we will provide a useful guide to be used by nutrition experts taking care of subjects with obesity. In particular, we will report recommendations on the correct use of this therapeutic approach for weight loss and management of side effects.